PKM2 Promotes Breast Cancer Progression by Regulating Epithelial Mesenchymal Transition - Hui Xiao; Longxiao Zhang; Yuan Chen; Chengjun Zhou; Xiao Wang; Dehai Wang; Zhenzhong Liu (Analytical Cellular Pathology)
Breast cancer is the leading cause of females characterized by high invasive potential. It is necessary to explore the underlying mechanism of breast cancer metastases and to find specific therapeutic targets. PKM2 is considered a new biomarker of cancer with upregulated expression in tumor tissue. PKM2 participates in the cancer-specific Warburg effect to regulate fast glucose intake consumption. Besides, PKM2 also contributes to cancer progression, especially tumor metastasis. In this study, we showed that PKM2 is upregulated in breast cancer tissues and the upregulating of PKM2 in breast cancer correlates with poor prognosis. PKM2 can regulate tumor progression by promoting tumor cell viability and mobility. Furthermore, overexpression of PKM2 can promote EMT to encourage tumor metastasis. These findings indicate PKM2 is a potentially useful diagnostic biomarker and therapeutic target in breast cancer.